Pengaruh Konseling Kesehatan Terhadap Penurunan Tingkat Kecemasan Pasien TBC Paru Di Puskesmas Campurejo Kota Kediri - Hengki Irawan (Akademi Keperawatan Dharma Husada Kediri, 2015)
Lung Tuberculosis germ. The treatment and supporting facilities have been available. The Government effort to overcome this disease by Directly Observed Treatment Shortcourse (DOTS). The old treatment and expensive cost caused the patient feels anxiety. The Nurse’s role is to overcome the anxiety through health counseling. It is a kind of method used to solve the patient’s problem. The research aims to know the influence of health counseling toward the reduction of anxiety level in lung TBC of the patient in Puskesmas Campurejo Kediri city. This research is called Pre-Experimental with One Group Pretest- Posttest design. The samples consists of 25 respondents, taken with Non Probability Sampling by type Pusposive Sampling Method, which new lung TBC patient’s. Variable Tuberculosis (TBC) is contagious disease caused by Mycobacterium measured in this research are patient’s anxiety level before and after given the health counseling. The result shows that before given the health counseling, 32% patient experience in low, middle, and high anxiety level, while 4% patient experience in panic. After given health counseling, the result shows that 44% patients experience in middle anxiety level, 36% patients experience in low anxiety level, 28% patients experience in high anxiety level. These data indicate that 28% respondents show the alteration in reduction of anxiety level, 72% do not show the alteration in reduction of anxiety level. The result shows that 80% respondents experience the alteration in reduction of anxiety level while 20% respondents do not experience this. Based on the results of Wilcoxon (α=5%), the level anxiety in health counseling of towards the reduction of anxiety level in Lung TBC of the patients. For the next research hope to make a contact and therapeuticall communication with patients. Key words: Lung TBC, anxiety level, health counseling